1931 Ill. Laws 452-53, An Act to Regulate the Sale, Possession and Transportation of Machine Guns, §§ 1-2 - (:unkn) unknown (General Publisher, 1931)
Prohibited selling, loaning, or giving away, purchasing, possessing, carrying, or transporting any machine gun.
--
Keywords: MACHINE GUN RESTRICTION